Peculiarities of formation of assembly supply in the supply chain - Фалович, Володимир Андрійович (Technology audit and production reserves, 2015)
The tendencies of logistics services market in Poland are investigated. It allows to reveal a positive influence of globalization and the entry of Poland into the EU on the development of road transport sector. It is identified that the trend accelerating industrial development in the country directly influence the development of the transport sector cooperation with industry manufacturers, creating new supply chains in which the carrier takes a leadership role, which associated compensation of rising transport costs by clients, thus transforming correlation trade off in correlation trade up. It is generalized an experience of assembly supply formation by large logistics operators in the use of industrial manufacturers models just in time, aimed at reducing the cost of warehousing and transportation in the area of supply of raw materials, components, finished product and marketing products to the final consumer. It is identified an expediency of carrier usage in the supply chain to coordinate the formation of teams and supplies to ensure their timeliness, reliability and confidentiality of customer information. It is identified that the study of life cycle of logistics services in Poland can be useful for Ukraine in period of out of the downturn in the economy that needs radical change, economic recovery processes in industry, implementation of integrated IT systems, use of tools to reduce costs.